A női genitális csonkítás: múlt és jelen: Történeti és gyakorlati helyzetkép Kenyában - Solymári, Dániel; Mangera, Janet; Csikós, Gabriella (Afrika Tanulmányok / Hungarian Journal of African Studies, 2019)
In this paper we briefly describe the historical context of the development of female genital mutilation and summarize the results of the most important sources. In addition to terminological and conceptual clarification, we describe the main types of practice. We draw attention to the health and medical aspects of its use and the possible consequences. Furthermore, we present a contemporary picture of its practice in Kenya and its legal and social situation. At the end of the essay, for the sake of understanding its personal and human ramifications, we briefly describe the results of a research on qualitative ‚snowball’ methods with former victims, revealing the psychosocial side of this practice.